Housing Demand in the Polish Peoples’ Republic - Jarmuż, Michał; Jarosz, Dariusz (Studia Historiae Oeconomicae, 2013)
Although historians and social scientists devoted considerable attention to issues related to housing in the Polish Peoples’ Republic era, many problems still need further research. The crucial problem of the paper is to find an answer to the question: what did Poles have to do in the period between 1944/45 and 1989 in order to obtain housing? The answer given is the effect of several years of primary source research which encompassed archival material of assorted types and origins.